The Role of ICT in Enhancing the Teaching Learning Process in Architecture Institutes (International Journal of Food and Nutritional Sciences, 2022)
Information and Communication technology has revolutionized various aspect of modern education including architecture study architecture institute have recognized the potential of ICT tools and technology in enhancing the teaching learning process this paper AIIMS to explore the multifaceted role of ICT in architecture institute analyzing its impact on teaching methods teaching outcomes and overall educational experiences through on insights into the integration of ICT in architecture education highlighting it's benefits challenges and potential developments